“LET THEM DREAM OF LIFE ETERNAL, WE SHALL LIVE IT”: GEORGE R. R. MARTIN’S FEVRE DREAM, SLAVERY AND VAMPIRES IN THE UNITED STATES OF AMERICA - Maia Baby Gomes, Arthur; Zanini, Claudio Vescia (Abusões, 2019)
Fevre Dream is a historical horror novel published by George R.R. Martin in 1982. Despite being frequently overlooked by scholarship on Martin’s oeuvre, it is an important novel not only because in it the author definitely embraces dark fantasy, but also because it uses vampirism as a tool for strong social criticism. This article describes how the slavery system is depicted in Fevre Dream in association with memories of slavery and vampirism, and it is structured in four sections: slavery memories produced in the United States after the 19th century; Abner Marsh, the protagonist; the dichotomy between the opposite vampiric forces repsented by Joshua York and Damon Julian; and the status of the black characters in the novel.